Method for preparing water-soluble composite salt core based on hot melt extrusion 3D printing technology

Through hot melt extrusion direct writing 3D printing technology, the coordinated regulation of material and process parameters is solved, and the problem of water-soluble composite salt core forming in the existing technology is achieved, efficient and precise complex structure forming is achieved, and the performance and production of salt core are improved. efficiency.

CN119500989AActive Publication Date: 2025-02-25CHINA UNIV OF GEOSCIENCES (WUHAN) +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411626604.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-quality water-soluble composite salt cores in the prior art, especially in low-melting point alloy castings such as aluminum (magnesium), and it is difficult to achieve efficient forming and cleaning of complex structures.

Method used

Using hot melt extrusion direct writing 3D printing technology, coordinated the parameters such as salt core material composition, heating temperature, extrusion direct writing 3D printing forming and step-by-step sintering process, and directly form complex special-shaped holes and runner structures to avoid Accuracy error caused by core assembly.

Benefits of technology

The rapid mold-free forming of water-soluble composite salt core with high precision, complete structure and dense structure is achieved, which improves bending strength and impact toughness, simplifies production processes and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500989A_ABST
    Figure CN119500989A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of casting, and particularly relates to a method for preparing a water-soluble composite salt core based on a hot-melt extrusion direct-writing 3D printing technology. The invention relates to a water-soluble composite salt core material, which is composed of the following components in percentage by mass: 50-70% of pretreated water-soluble inorganic salt, 20-50% of binder and 0-10% of enhancer, and the ratio of the pretreated water-soluble inorganic salt to the binder to the enhancer is (50-70%): (20-50%): (0-10%). The water-soluble composite salt core prepared by the invention can realize rapid die-free forming, and the shrinkage rate, bending strength, water dissolution rate, moisture absorption rate and other properties of the water-soluble salt core can be comprehensively regulated and controlled by adjusting the proportion of the materials in the slurry. In addition, the raw materials are low in price, the equipment cost is low, the process is simple and environment-friendly, and the development of green manufacturing can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of casting technology, and more specifically, relates to a method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology. Background Art

[0002] With the rapid development of my country's aviation, aerospace, automobile manufacturing, and 5G communications, the demand for complex thin-walled precision castings of low-melting-point alloys such as aluminum (magnesium) is also increasing. Such castings often have complex inner cavity structures, some of which are basically closed or have many slender curved channels of different shapes. Prefabricated cores are required to cast the complex inner cavity structure and remove the core after the casting is formed. In order to form high-quality precision castings, higher requirements are placed on the performance of the casting core and its forming and cleaning methods.

[0003] The casting core must have high room temperature strength and dimensional accuracy, good high temperature stability and air permeability, small gas emission, and excellent post-casting disintegration and cleaning performance; the commonly used casting core materials such as resin sand cores, silicon oxide and alumina-based ceramic cores cannot meet the above performance requirements at the same time, and all need to use mixed alkali method, alkali solution method, pressure core removal method and hydrofluoric acid method to clean the residual cores in the inner cavity of the casting and the curved channels. It is very difficult to clean the residual cores in the nearly closed inner cavity of the casting. Among the above core cleaning methods, some will corrode the casting, some will produce toxic substances to pollute the environment, and some have complex core removal processes and require special equipment (such as pressure core removal method). Water-soluble salt core technology can solve the problem of cleaning casting core materials very well. After the casting is formed, the residual core can be quickly cleaned by dissolving it with water, which can save labor and improve the working environment.

[0004] At present, it is difficult to directly form this type of complex salt core as a whole. Traditional preparation processes include melt casting, pressing and sintering, and bonding forming. The melt casting method requires block forming and assembly through a mold, which is a complex process and has low preparation efficiency; the pressing and sintering method has high preparation costs, complex preparation processes, and high equipment requirements; the salt cores prepared by the bonding forming method have low mechanical properties and low water solubility rates. Therefore, the water-soluble salt cores prepared by traditional processes are difficult to meet the requirements of die-casting production, and the preparation of integrated, complex, and precise water-soluble salt cores has become a key problem in the manufacture of cavity die-castings of low-melting-point alloy castings such as aluminum (magnesium).

[0005] CN 104399865A discloses a water-soluble graphite composite salt core material, a graphite composite salt core and a preparation method thereof, which are mainly used for casting of cooling oil channels in aluminum pistons. The material of the graphite composite salt core includes a water-soluble metal halide (a single metal halide or a mixture of multiple metal halides) and graphite powder, and the preparation method is a pressing and sintering method. The salt core prepared by the method has high strength and low shrinkage, but the graphite powder and the metal halide are easily mixed unevenly, resulting in stratification of the salt core, which affects the performance of the salt core.

[0006] CN 106670376A discloses a high-strength composite salt core for casting low-melting alloys, wherein the components of the water-soluble salt core include water-soluble inorganic salts and reinforcing agents, wherein the inorganic salts include a low-melting inorganic salt and more than one high-melting inorganic salt. The low-melting inorganic salts are potassium nitrate and sodium nitrate, and the high-melting inorganic salts are potassium chloride, potassium bromide, sodium chloride and sodium bromide. The reinforcing agent includes one or more of dalin sand, refractory mud powder, glass fiber powder, kaolin, quartz powder, bentonite, alumina powder and high-alumina bauxite. The preparation of the salt core adopts a melt casting method, and the prepared salt core has high strength and low moisture absorption rate. However, the low-melting salt determines the melting point of the overall salt core, so the salt core is only suitable for casting low-melting alloys, and cannot meet the casting requirements of low-melting alloys such as aluminum (magnesium).

[0007] CN 115815532A discloses a water-soluble salt core material and a preparation method and application thereof, wherein the components of the water-soluble salt core include an inorganic salt and a binder, wherein the inorganic salt is a single salt with a high melting point, including one of sodium chloride, potassium chloride, sodium sulfate or potassium sulfate, and the binder includes two or more of an organic binder and an inorganic binder, one of which is bentonite. The salt core is prepared by extrusion molding. Although the preparation process is simple and a water-soluble salt core with a complex shape can be formed, the salt core composed of a single inorganic salt has a lower strength than a composite salt core, and the mechanical properties need to be improved.

[0008] The preparation method of the above-mentioned water-soluble salt core includes traditional preparation processes and emerging preparation processes. However, in order to achieve high-efficiency and high-quality simultaneous production of water-soluble salt cores of low-melting-point alloy castings such as aluminum (magnesium) with slender and curved internal channels and complex spatial structures, it is necessary to further optimize the material composition and preparation method of the salt core and seek a more complete preparation plan. Summary of the invention

[0009] In view of the deficiencies and improvement needs of the prior art, the present invention provides a method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology, which is mainly used for low melting point alloy castings such as aluminum (magnesium) with complex internal structures. By synergistically regulating parameters such as salt core material composition, heating temperature, extrusion direct writing 3D printing forming and step-by-step sintering process, complex special-shaped holes, runners and other structures can be directly formed as a whole, avoiding the precision error caused by core assembly, and has a good application prospect in complex core material systems and new product research and development, and can be used for moldless rapid overall direct forming of complex casting cores.

[0010] A water-soluble composite salt core material, consisting of the following components:

[0011] The water-soluble inorganic salt, the binder and the reinforcing agent are pretreated, and the weight percentage is as follows: the pretreated water-soluble inorganic salt: the binder: the reinforcing agent = 50%-70%: 20%-50%: 0%-10%.

[0012] Furthermore, the pre-treated water-soluble inorganic salt is obtained by mixing a coating solution with an inorganic salt powder system, and in terms of mass percentage, water-soluble inorganic salt: coating solution = 40%-60%: 40%-60%;

[0013] The inorganic salt powder system is at least two of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride;

[0014] The inorganic salt powder system has a melting point of 450-1200°C and a particle size of 500-3000 mesh;

[0015] The coating solution is prepared from polydimethylsiloxane and anhydrous ethanol.

[0016] Furthermore, the binder is one of carrageenan solution, starch solution, xanthan gum solution, sodium alginate solution, konjac gum solution, sodium carboxymethyl cellulose solution and agar solution, and the concentration of the binder is 0.1% to 15%.

[0017] Furthermore, the reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes.

[0018] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0019] S1. 3D printing of the salt core blank: preparing a salt-based slurry, and using a heatable direct-writing 3D printing device to 3D print the salt-based slurry at a temperature of 25° C. to 220° C. to obtain a salt core blank;

[0020] Wherein, the salt-based slurry is the above-mentioned water-soluble composite inorganic salt material or binder;

[0021] S2. Sintering of the water-soluble composite salt core: After the salt core green body is naturally dried, it is transferred to a high-temperature sintering furnace for sintering to obtain the water-soluble composite salt core.

[0022] Furthermore, in step S1, when the salt-based slurry is a water-soluble composite inorganic salt material, the preparation method of the salt-based slurry is:

[0023] The inorganic salt powder system is coated with a coating solution to obtain a pretreated water-soluble inorganic salt, the pretreated water-soluble inorganic salt and an enhancer are mixed evenly in proportion to obtain a mixed powder, a binder is added to the mixed powder, and the mixture is heated and stirred to obtain a uniformly mixed salt-based slurry; in terms of mass percentage, the pretreated water-soluble inorganic salt: binder: enhancer = 50%-70%: 20%-50%: 0%-10%.

[0024] Further, in step S1, when the salt-based slurry is used as a binder, graphite powder is added to the binder, and in terms of mass percentage, graphite powder: binder = 60%-70%: 30%-40%.

[0025] Furthermore, the binder in the salt-based slurry and the binder in the water-soluble composite inorganic salt material are both one of carrageenan solution, starch solution, xanthan gum solution, sodium alginate solution, konjac gum solution, sodium carboxymethyl cellulose solution and agar solution, and the concentration of the binder is 0.1% to 15%.

[0026] Furthermore, in step S2, the sintering is carried out by combining step-by-step sintering and liquid phase sintering, and the final sintering temperature is 450° C. to 1200° C.;

[0027] The specific sintering steps are as follows: firstly heat to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes to remove the binder, dispersant and defoamer in the green body; then heat at a heating rate of 1-3°C / min, and keep at 5-30°C from the final firing temperature for 30-60 minutes; then heat to the final firing temperature at a heating rate of 5°C / min, and keep at a temperature of 10-30 minutes; then cool to 5-30°C below the final firing temperature, and keep at a temperature of 30-60 minutes; finally cool to room temperature with the furnace.

[0028] Further, in step S2, the inner diameter of the printing needle is 0.61 mm to 3.8 mm, and the extrusion air pressure is 10 psi to 60 psi.

[0029] In general, the water-soluble salt core material and preparation method of the present invention have the following main advantages compared with the prior art:

[0030] (1) Compared with the traditional method of preparing water-soluble salt cores, the advantage of hot melt extrusion 3D printing technology in preparing water-soluble salt cores is that parts can be quickly formed without molds, and the process is simple, the raw material cost is low, and the equipment requirements are low. It can achieve moldless rapid and precise forming of high-precision complex salt cores, obtain salt cores with complete structure, dense organization, and high precision, and solve the problem of difficulty in overall forming of complex salt cores.

[0031] (2) In order to solve the problem that it is difficult to simultaneously improve the flexural strength and impact toughness of the existing salt core, the flexural strength and impact toughness of the composite salt core are simultaneously improved by the multi-phase hybrid coupling of inorganic salts and reinforcing agents.

[0032] (3) After the inorganic salt powder is coated, a hydrophobic barrier is formed on the surface of the inorganic salt powder particles to prevent the inorganic salt from dissolving when using a water-based binder, thereby expanding the selection range of the binder solution and having more environmental and cost advantages.

[0033] (4) The salt-based slurry prepared with a heat-fusible binder does not require ball milling, and the green body can be transferred to a high-temperature sintering furnace for sintering in a short time after being formed, which shortens the production cycle to a certain extent.

[0034] (5) By adjusting the solid content of the slurry (by adjusting the mass proportion of the inorganic salt powder in the total slurry), the surface accuracy, bending strength and linear shrinkage rate of the salt core can be controlled. By adjusting the direct writing forming parameters (filling rate, printing speed, needle inner diameter and filling line angle, etc.), the complete formability, surface quality, dimensional accuracy and strength of the blank can be coordinated and regulated.

[0035] (6) The sintering process adopts a combination of step-by-step sintering and liquid phase sintering. Step-by-step sintering can reduce cracks and deformation caused by sudden temperature changes by controlling the heating rate and holding time; liquid phase sintering helps to evenly distribute and better bond the particles, further optimize the microstructure of the material, improve the bending strength of the salt core, and also avoid over-sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the preparation process of the water-soluble composite salt core. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0038] The physical and chemical parameters of the sodium chloride powder used in the present invention are shown in Table 1:

[0039] Table 1

[0040]

[0041] The physical and chemical parameters of the sodium carbonate powder used in the present invention are shown in Table 2:

[0042] Table 2

[0043]

[0044] The physicochemical parameters of the potassium carbonate powder used in the present invention are shown in Table 3:

[0045] Table 3

[0046]

[0047] The physical and chemical parameters of the calcium carbonate powder used in the present invention are shown in Table 4:

[0048]

[0049] Table 4 The physicochemical parameters of potassium chloride powder used in the present invention are shown in Table 5:

[0050] Table 5

[0051]

[0052] The physical and chemical parameters of the magnesium chloride powder used in the present invention are shown in Table 6:

[0053] Table 6

[0054]

[0055] The physical and chemical parameters of the calcium chloride powder used in the present invention are shown in Table 7:

[0056] Table 7

[0057]

[0058] The physical and chemical parameters of the barium chloride powder used in the present invention are shown in Table 8:

[0059] Table 8

[0060]

[0061] The physical and chemical parameters of the bauxite powder used in the present invention are shown in Table 9:

[0062] Table 9

[0063]

[0064]

[0065] The physical and chemical parameters of the glass fiber used in the present invention are shown in Table 10:

[0066] Table 10

[0067]

[0068] The physical and chemical parameters of the mullite powder used in the present invention are shown in Table 11:

[0069] Table 11

[0070]

[0071] The physical and chemical parameters of the sericite used in the present invention are shown in Table 12:

[0072] Table 12

[0073]

[0074] The present invention is to protect a water-soluble composite salt core material, which is composed of the following components:

[0075] The water-soluble inorganic salt, the binder and the reinforcing agent are pretreated, and the weight percentage is as follows: the pretreated water-soluble inorganic salt: the binder: the reinforcing agent = 50%-70%: 20%-50%: 0%-10%.

[0076] Wherein, the pretreatment water-soluble inorganic salt is obtained by mixing a coating solution with an inorganic salt powder system, and in terms of mass percentage, the water-soluble inorganic salt: coating solution=40%-60%:40%-60%, the inorganic salt powder system is at least two of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride, the melting point of the inorganic salt powder system is 450-1200° C., and the particle size is 500-3000 mesh; the coating solution is a non-aqueous coating, preferably an organosilicon solution, the organosilicon solution is prepared by polydimethylsiloxane and anhydrous ethanol, and the concentration is 50wt.%; the binder is one of a carrageenan solution, a starch solution, a xanthan gum solution, a sodium alginate solution, a konjac gum solution, a sodium carboxymethylcellulose solution and an agar solution, the concentration of the binder is 0.1%-15%, and the solvent is water. The reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes.

[0077] The present invention also protects a method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology, which specifically includes the following steps:

[0078] (1) Preparation of salt-based slurry

[0079] The salt-based slurry is the above-mentioned water-soluble composite inorganic salt material or binder, and:

[0080] When the salt-based slurry is the above-mentioned water-soluble composite inorganic salt material, the preparation method of the water-soluble composite inorganic salt material is:

[0081] Two or more inorganic salt powders are coated with a coating solution to obtain a pretreated water-soluble inorganic salt. The pretreated water-soluble inorganic salt and the reinforcing agent are mixed evenly in proportion to obtain a mixed powder. The mixed powder is added to the binder solution in small amounts and repeatedly and heated and stirred continuously to obtain a uniformly mixed salt-based slurry. The mass percentage of each component is preferably as follows: 50% to 70% of the pretreated water-soluble inorganic salt, 20% to 50% of the binder, and 0% to 10% of the reinforcing agent.

[0082] When the salt-based slurry is used as a binder, graphite powder is added to the binder as a supporting material, and the mass percentage is graphite powder: binder = 60%-70%: 30%-40%.

[0083] (2) 3D printing of salt core blanks

[0084] The salt-based slurry is loaded into the extrusion barrel of the heatable direct writing 3D printing device while hot, and the temperature control and the motion trajectory route of the extruder and the extrusion state are controlled by the host computer slicing software. The salt-based slurry is deposited on the substrate according to the preset route to form a salt core blank. Among them, the temperature control range of the extrusion barrel is 25℃~220℃, and after heating to the required temperature until the material is completely in a molten state (if heating is not required, the temperature is set to 25℃), the blank is printed and formed by adjusting the printing parameters; in the process of direct writing of the salt-based slurry to form the salt core blank, the forming process parameters are preferably as follows: the inner diameter of the needle is 0.61mm~3.8mm, and the extrusion pressure is 10psi~60psi. Among them, the heatable direct writing 3D printing device is a prior art, such as the 3D printing device recorded in the patent number CN202311075788.8 and the patent name of a double-head collaborative direct writing 3D printing device can be used as a specific embodiment of the heatable direct writing 3D printing device of the present invention.

[0085] (3) Sintering of water-soluble composite salt core

[0086] After 24 hours of natural drying, the salt core green body is transferred to a high-temperature sintering furnace for sintering. It is sintered at a relatively high temperature for a certain period of time to form better strength and other properties and to play the role of the reinforcing agent in enhancing the green body performance, thereby obtaining a high-strength water-soluble composite salt core.

[0087] The sintering conditions in step (3) are preferably as follows: a combination of step-by-step sintering and liquid phase sintering is used, and the final sintering temperature is 450°C to 1200°C. The specific sintering steps are: first, heating from room temperature to 200°C at a heating rate of 1°C / min, then heating from 200°C to 300°C at a heating rate of 0.5°C / min, and then heating from 300°C to 360°C at a heating rate of 0.75°C / min, and keeping at 360°C for 60 minutes to remove the binder and other organic matter in the green body; then heating at a heating rate of 1 to 3°C / min, keeping at 5 to 30°C from the final sintering temperature, and keeping for 30 minutes to 60 minutes; then heating to the final sintering temperature at a heating rate of 5°C / min, and keeping for 10 minutes to 30 minutes; then cooling to 5 to 30°C below the final sintering temperature, and keeping for 30 minutes to 60 minutes; finally cooling to room temperature with the furnace. The purpose of liquid phase sintering is to improve the bending strength of the salt core and avoid over-sintering.

[0088] In the present invention, by using a binder as a salt-based slurry and graphite powder as a supporting material, since graphite powder is easily burned out under sintering conditions of 500-600°C, a water-soluble salt core with a suspended structure can be prepared, which can be applied to aluminum alloy components with complex internal structures and suspended channels.

[0089] It should be noted that Examples 1-8 all use a heatable direct-write 3D printing device, the computer-side control software is the Simplify 3D slicing software, and the size of the printed body is 60 mm×10 mm×6 mm.

[0090] <Example 1>

[0091] The interfacial binding energy of NaCl(100) / Na2CO3(100) was calculated to be 13.2 J / m by first principle calculation. 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3 as the matrix material.

[0092] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0093] Sodium chloride (D50=10 μm) and sodium carbonate (D50=6.5 μm) are uniformly mixed in a ratio of 30 mol% NaCl-70 mol% Na2CO3 to obtain an inorganic salt powder system; the inorganic salt powder system is coated with an organic silicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 4:6.

[0094] Carrageenan and deionized water were used to prepare a binder solution with a mass fraction of 0.5% under heating conditions at 80°C.

[0095] 62 parts by mass of pretreated water-soluble inorganic salt and 10 parts by mass of bauxite powder were mixed evenly, and added into the heated and stirred carrageenan solution (28 parts by mass) in small amounts and several times until the pretreated water-soluble inorganic salt, bauxite powder and carrageenan solution were evenly mixed.

[0096] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 85°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 23° / -67° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 10psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0097] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 600°C and keep for 60 minutes; then heat to 620°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 600°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0098] <Example 2>

[0099] The interfacial binding energy of NaCl(100) / K2CO3(011) was calculated to be 1.04 J / m by first principle calculation. 2 , a water-soluble composite salt core was prepared using NaCl / K2CO3 as the matrix material.

[0100] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0101] Sodium chloride (D50=10 μm) and potassium carbonate (D50=5 μm) are uniformly mixed in a ratio of 50 mol% NaCl-50 mol% K2CO3, and the inorganic salt powder system is coated with an organic silicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 4:6.

[0102] A binder solution with a mass fraction of 10% was prepared by using starch and deionized water under heating conditions of 100°C.

[0103] 70 parts by mass of pretreated water-soluble inorganic salt and 5 parts by mass of glass fiber are mixed evenly, and added into the starch solution (25 parts by mass) which is being heated and stirred in small amounts and several times until the pretreated water-soluble inorganic salt, glass fiber and starch solution are evenly mixed.

[0104] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 90°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.84mm extruder head was selected for printing. The extrusion pressure was 30psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0105] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 620°C and keep for 60 minutes; then heat to 640°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 620°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0106] <Example 3>

[0107] The interfacial binding energy of NaCl(100) / CaCO3(010) was calculated to be 0.12 J / m 2 , NaCl-CaCO3 was used as the matrix material to prepare the water-soluble composite salt core.

[0108] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0109] Sodium chloride (D50=10 μm) and calcium carbonate (D50=5 μm) are uniformly mixed in a ratio of 60 mol% NaCl-40 mol% CaCO3, and the mixed powder is coated with an organosilicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organosilicon solution is 4:6.

[0110] Agar and deionized water were used to prepare a binder solution with a mass fraction of 1% under heating conditions of 80°C.

[0111] 66 parts by mass of pretreated water-soluble inorganic salt and 2 parts by mass of mullite powder were mixed evenly, and added in small amounts to the agar solution (32 parts by mass) being heated and stirred until the pretreated water-soluble inorganic salt, mullite powder and agar solution were evenly mixed.

[0112] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: the barrel heating temperature was 80°C, the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 0° / 90° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 30psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0113] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 770°C and keep for 60 minutes; then heat to 790°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 770°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0114] <Example 4>

[0115] The interfacial binding energy of NaCl(100) / KCl(101) was calculated to be 0.05 J / m by first principle calculation. 2 , using NaCl-KCl as the matrix material to prepare the water-soluble composite salt core.

[0116] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0117] Sodium chloride (D50=10 μm) and potassium chloride (D50=5 μm) are uniformly mixed in a ratio of 50 mol% NaCl-50 mol% KCl, and the mixed powder is coated with an organosilicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organosilicon solution is 4:6.

[0118] Konjac gum and deionized water were used to prepare a binder solution with a mass fraction of 5% under a heating condition of 90°C.

[0119] 67 parts by mass of pretreated water-soluble inorganic salt and 8 parts by mass of sericite were mixed evenly, and added into the heated and stirred konjac gum solution (25 parts by mass) in small amounts and several times until the pretreated water-soluble inorganic salt, sericite and konjac gum solution were evenly mixed.

[0120] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 90°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.84mm extruder head was selected for printing. The extrusion pressure was 30psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0121] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 660°C and keep for 60 minutes; then heat to 680°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 660°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0122] <Example 5>

[0123] The interfacial binding energy of NaCl(100) / Na2CO3(100) / MgCl2(100) was calculated to be 14.03 J / m by first principle. 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-MgCl2 as the matrix material.

[0124] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0125] Sodium chloride (D50=10μm), sodium carbonate (D50=6.5μm) and magnesium chloride (D50=5μm) are uniformly mixed in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% MgCl2, and the mixed powder is coated with an organosilicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system and the organosilicon solution is 5:5.

[0126] Carrageenan and deionized water were used to prepare a binder solution with a mass fraction of 0.5% under heating conditions at 80°C.

[0127] 68 parts by mass of pretreated water-soluble inorganic salt and 8 parts by mass of bauxite powder were mixed evenly, and added into the heated and stirred carrageenan solution (24 parts by mass) in small amounts and several times until the pretreated water-soluble inorganic salt, bauxite powder and carrageenan solution were evenly mixed.

[0128] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 80°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 50psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0129] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 420°C and keep for 60 minutes; then heat to 450°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 420°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0130] <Example 6>

[0131] The interfacial binding energy of NaCl(100) / Na2CO3(100) / CaCl2(110) was calculated to be 16.06 J / m 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-CaCl2 as the matrix material.

[0132] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0133] Sodium chloride (D50=10μm), sodium carbonate (D50=6.5μm) and calcium chloride (D50=5μm) are uniformly mixed in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% BaCl2, and the mixed powder is coated with an organosilicon solution to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system and the organosilicon solution is 5:5.

[0134] Carrageenan and deionized water were used to prepare a binder solution with a mass fraction of 0.5% under heating conditions at 80°C.

[0135] 68 parts by mass of pretreated water-soluble inorganic salt and 8 parts by mass of bauxite powder were mixed evenly, and added into the heated and stirred carrageenan (24 parts by mass) in small amounts and several times until the pretreated water-soluble inorganic salt, bauxite powder and carrageenan solution were evenly mixed.

[0136] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 80°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 50psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0137] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 600°C and keep for 60 minutes; then heat to 630°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 600°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0138] <Example 7>

[0139] The first principle calculations revealed that the interface binding energy of NaCl / Na2CO3 / BaCl2 is 37 J / m 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-BaCl2 as the matrix material.

[0140] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0141] Sodium chloride (D50 = 10 μm), sodium carbonate (D50 = 6.5 μm) and barium chloride (D50 = 5 μm) are mixed evenly in a ratio of 25 mol% NaCl-58 mol% Na2CO3-17 mol% BaCl2, and the mixed powder is coated with an organic silicon solution to obtain a pre-treated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 5:5. A binder solution with a mass fraction of 0.5% is prepared using carrageenan and deionized water under heating conditions of 80°C. 68 parts by mass of the pre-treated water-soluble inorganic salt and 8 parts by mass of bauxite powder are mixed evenly, and added in small amounts and multiple times to the carrageenan solution (24 parts by mass) that is being heated and stirred until the pre-treated water-soluble inorganic salt, bauxite powder and carrageenan solution are evenly mixed.

[0142] The printing process parameters were set in the upper computer slicer software of the heatable direct-write 3D printing device: barrel heating temperature was 80°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 50psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0143] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 600°C and keep for 60 minutes; then heat to 630°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 600°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0144] <Example 8>

[0145] The first principle calculations revealed that the interface binding energy of NaCl / Na2CO3 / BaCl2 is 37 J / m 2 , NaCl-Na2CO3-BaCl2 is used as the matrix material to prepare the water-soluble composite salt core, and graphite powder is used as the matrix material to prepare the supporting material of the water-soluble composite salt core.

[0146] A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology specifically comprises the following steps:

[0147] Sodium chloride (D50 = 10 μm), sodium carbonate (D50 = 6.5 μm) and barium chloride (D50 = 5 μm) are mixed evenly in a ratio of 25 mol% NaCl-58 mol% Na2CO3-17 mol% BaCl2, and the mixed powder is coated with an organic silicon solution to obtain a pre-treated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 5:5. A binder solution with a mass fraction of 0.5% is prepared using carrageenan and deionized water under heating conditions of 80°C. 68 parts by mass of the pre-treated water-soluble inorganic salt and 8 parts by mass of bauxite powder are mixed evenly, and added in small amounts and multiple times to the carrageenan solution (24 parts by mass) that is being heated and stirred until the pre-treated water-soluble inorganic salt, bauxite powder and carrageenan solution are evenly mixed.

[0148] Graphite powder (D50 = 5 μm) was coated with an organosilicon solution to obtain pretreated graphite powder, wherein the mass ratio of graphite powder to organosilicon solution was 6:4. A binder solution with a mass fraction of 0.5% was prepared using carrageenan and deionized water under heating conditions of 80°C. 72 parts by mass of pretreated graphite powder were added in small amounts to the heated and stirred carrageenan solution (28 parts by mass) until the pretreated graphite powder and the carrageenan solution were evenly mixed.

[0149] The printing process parameters were set in the host computer slicing software of the dual extruder 3D printing device: barrel heating temperature was 80°C, filling rate was 100%, printing speed was 600mm / min, filling line angle was 45° / -45° composite filling. The evenly stirred salt-based slurry and graphite-based slurry were loaded into two extrusion barrels respectively, and a 0.61mm extruder was used for printing. The extrusion pressure was 50psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate and placed in the air to dry naturally for 24 hours.

[0150] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: first, heat from room temperature to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes; then heat at a heating rate of 3°C / min, heat to 600°C and keep for 60 minutes; then heat to 630°C at a heating rate of 5°C / min and keep for 30 minutes; then cool to 600°C and keep for 60 minutes; finally cool to room temperature with the furnace. After sintering, the final water-soluble composite salt core product with a suspended structure is obtained.

[0151] <Comparative Example 1>

[0152] Sodium chloride (D50 = 10 μm) and sodium carbonate (D50 = 6.5 μm) are uniformly mixed in a ratio of 30 mol% NaCl-70 mol% Na2CO3 to obtain an inorganic salt powder system;

[0153] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix the inorganic salt powder system and the polyvinyl pyrrolidone solution in a mass ratio of 8:2 to obtain a mixed slurry. Slowly pour the mixed slurry into the mold, let it stand for a while, and after the slurry is solidified and formed, demold it to obtain a wet blank.

[0154] The wet blank was placed in a drying oven and dried at 80°C for 12 hours to obtain a dry blank, which was sintered in a step-by-step sintering manner to obtain a sintered body. The specific sintering steps were as follows: first, heated from room temperature to 200°C at a heating rate of 1°C / min, then heated from 200°C to 300°C at a heating rate of 0.5°C / min, and then heated from 300°C to 360°C at a heating rate of 0.75°C / min, and kept at 360°C for 60 minutes; then heated at a heating rate of 3°C / min to 600°C and kept for 60 minutes; then heated to 620°C at a heating rate of 5°C / min and kept for 30 minutes; then cooled to 600°C and kept for 60 minutes; finally cooled to room temperature with the furnace. After sintering, the final water-soluble composite salt core product was obtained.

[0155] The water-soluble composite salt cores prepared in Examples 1-8 were tested for performance, and the results are shown in Table 13:

[0156]

[0157]

[0158] Table 13 Water-soluble composite salt core experimental data

[0159] In summary, Examples 1-8 are water-soluble composite salt cores prepared by the present invention, which have excellent bending strength, high surface quality, excellent water solubility rate and low moisture absorption rate, and have excellent comprehensive performance, and can meet the process requirements of precision casting of complex parts.

[0160] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A water-soluble composite salt core material, characterized in that: It is composed of the following components: The water-soluble inorganic salt, the binder and the reinforcing agent are pretreated, and the weight percentage is as follows: the pretreated water-soluble inorganic salt: the binder: the reinforcing agent = 50%-70%: 20%-50%: 0%-10%.

2. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The pre-treated water-soluble inorganic salt is obtained by mixing a coating solution with an inorganic salt powder system, and the water-soluble inorganic salt: coating solution = 40%-60%: 40%-60% by mass percentage; The inorganic salt powder system is at least two of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride; The inorganic salt powder system has a melting point of 450-1200°C and a particle size of 500-3000 mesh; The coating solution is prepared from polydimethylsiloxane and anhydrous ethanol.

3. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The binder is one of carrageenan solution, starch solution, xanthan gum solution, sodium alginate solution, konjac gum solution, sodium carboxymethyl cellulose solution and agar solution, and the concentration of the binder is 0.1% to 15%.

4. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes.

5. A method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology, characterized in that: The specific steps include: S1. 3D printing of the salt core blank: preparing a salt-based slurry, and using a heatable direct-writing 3D printing device to 3D print the salt-based slurry at a temperature of 25° C. to 220° C. to obtain a salt core blank; Wherein, the salt-based slurry is the water-soluble composite inorganic salt material or binder as described in any one of claims 1 to 4; S2. Sintering of the water-soluble composite salt core: After being naturally dried, the salt core green body is transferred to a high-temperature sintering furnace for sintering to obtain a water-soluble composite salt core.

6. The method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology according to claim 5, characterized in that: In step S1, when the salt-based slurry is a water-soluble composite inorganic salt material, the preparation method of the salt-based slurry is: The inorganic salt powder system is coated with a coating solution to obtain a pretreated water-soluble inorganic salt, the pretreated water-soluble inorganic salt and an enhancer are mixed evenly in proportion to obtain a mixed powder, a binder is added to the mixed powder, and the mixture is heated and stirred to obtain a uniformly mixed salt-based slurry; in terms of mass percentage, the pretreated water-soluble inorganic salt: binder: enhancer = 50%-70%: 20%-50%: 0%-10%.

7. The method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology according to claim 5, characterized in that: In step S1, when the salt-based slurry is used as a binder, graphite powder is added to the binder, and the ratio by mass percentage is graphite powder: binder = 60%-70%: 30%-40%.

8. The method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology according to claim 7, characterized in that: The binder in the salt-based slurry and the binder in the water-soluble composite inorganic salt material are both one of carrageenan solution, starch solution, xanthan gum solution, sodium alginate solution, konjac gum solution, sodium carboxymethyl cellulose solution and agar solution, and the concentration of the binder is 0.1% to 15%.

9. The method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology according to claim 7, characterized in that: In step S2, the sintering is carried out by combining step-by-step sintering and liquid phase sintering, and the final sintering temperature is 450° C. to 1200° C.; The specific sintering steps are as follows: firstly heat to 200°C at a heating rate of 1°C / min, then heat from 200°C to 300°C at a heating rate of 0.5°C / min, and then heat from 300°C to 360°C at a heating rate of 0.75°C / min, and keep at 360°C for 60 minutes to remove the binder, dispersant and defoamer in the green body; then heat at a heating rate of 1-3°C / min, and keep at 5-30°C from the final firing temperature for 30-60 minutes; then heat to the final firing temperature at a heating rate of 5°C / min, and keep at a temperature of 10-30 minutes; then cool to 5-30°C below the final firing temperature, and keep at a temperature of 30-60 minutes; finally cool to room temperature with the furnace.

10. The method for preparing a water-soluble composite salt core based on hot melt extrusion direct writing 3D printing technology according to claim 7, characterized in that: In step S2, the inner diameter of the printing needle is 0.61 mm to 3.8 mm, and the extrusion air pressure is 10 psi to 60 psi.

Citation Information

Patent Citations

  • Water-soluble graphite composited salt core material, graphite composited salt core and preparation method thereof

    CN104399865A

  • Double-head collaborative direct-writing type 3D printing device and method

    CN117261207A

  • High-strength composite salt core material for low-melting-point alloy casting, salt core and preparation method

    CN106670376A

  • Coated sand, production method for same, and production method for casting mold

    CN111511483A

  • Method for producing moulds and cores suitable for producing fibre composite bodies or cast parts in metal or plastic, mould base material and binder used in method and moulds and cores produced according to method

    CN112166000A